Measurement of the inclusive jet cross-section in pp collisions at [Formula: see text] and comparison to the inclusive jet cross-section at [Formula: see text] using the ATLAS detector - ATLAS Collaboration; Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O S; et al. (The European physical journal. C, Particles and fields, 2013)
The inclusive jet cross-section has been measured in proton-proton collisions at [Formula: see text] in a dataset corresponding to an integrated luminosity of [Formula: see text] collected with the ATLAS detector at the Large Hadron Collider in 2011. Jets are identified using the anti-kt algorithm with two radius parameters of 0.4 and 0.6. The inclusive jet double-differential cross-section is presented as a function of the jet transverse momentum pT and jet rapidity y, covering a range of 20≤pT<430 GeV and |y|<4.4. The ratio of the cross-section to the inclusive jet cross-section measurement at [Formula: see text], published by the ATLAS Collaboration, is calculated as a function of both transverse momentum and the dimensionless quantity [Formula: see text], in bins of jet rapidity. The systematic uncertainties on the ratios are significantly reduced due to the cancellation of correlated uncertainties in the two measurements. Results are compared to the prediction from next-to-leading order perturbative QCD calculations corrected for non-perturbative effects, and next-to-leading order Monte Carlo simulation. Furthermore, the ATLAS jet cross-section measurements at [Formula: see text] and [Formula: see text] are analysed within a framework of next-to-leading order perturbative QCD calculations to determine parton distribution functions of the proton, taking into account the correlations between the measurements.